Creación del manual denominado: el juicio de amparo indirecto llevadito de la mano - Rosas Baqueiro, Marco Polo (Universidad Michoacana de San Nicolás de Hidalgo, 2021)
The following work purpose is the creation of a manual that would allow one to have a full picture about the indirect amparo, in both instances, and in every subject. The aforementioned, mainly through fieldwork and with support in the legislation alongside its jurisprudential interpretation. It has the main objective of preparing the new generations of lawyers, making them skillful in their job at federal courts, by means of including all that is investigated and researched in the programs according to the bachelor degree and even further degrees. This work touches topics such as amparo against laws, substantiation and resolution of the direct amparo, alongside the resolution and procedure of different resources and incidents that may appear on this trial, and also, the procedures to achieve the fulfillment of amparo sentences through the explication of amparo´s trial principles, the different parts that intervene and how they participate, inadmissibility, dismissal, the substantiation of the procedure, competence, impediments, legitimation, legal claim requirements, the initial accord of prevention, discardment of the legal claim or the admission of it, notifications, justified informs and their requirements, incidents, proof, constitutional hearing and its suspension or deferral, the sentence, alongside its theoretical, practical and forensic style requirements, suspension of the reclaimed act, principal and accessory resolutions within the suspension, sentence fulfillment, resources and amparo in diverse subjects.

El presente trabajo tiene como finalidad la creación de un manual que permita tener un panorama completo del amparo indirecto, en ambas instancias y en todas las materias. Lo anterior, mediante un trabajo preponderantemente de campo y con apoyo en la legislación y su interpretación jurisprudencial. Tiene el propósito de preparar a las nuevas generaciones de abogados en la pericia del ejercicio profesional frente a los tribunales federales, mediante la inclusión de lo investigado en los programas de estudio de licenciatura o posgrado en derecho. Aborda el amparo contra leyes; el trámite y resolución del amparo indirecto; trámite y resolución de recursos y del incidente de suspensión del acto reclamado y de las diversas incidencias que aparecen en este juicio, así como los procedimientos para lograr el cumplimiento de las sentencias de amparo a través de la explicación de los principios del juicio de amparo; las partes que intervienen y cómo participan; la improcedencia; el sobreseimiento; la substanciación del procedimiento: competencia; Impedimentos; legitimación; requisitos de la demanda; auto inicial de prevención, desechamiento o admisión; notificaciones; informe justificado y sus requisitos; incidentes; pruebas; audiencia constitucional y su suspensión o diferimiento; la sentencia con sus requisitos teóricos, prácticos y de estilo forense; la suspensión del acto reclamado; resoluciones principales y accesorias dentro de la suspensión; el cumplimiento de sentencias; los recursos y el amparo en las diferentes materias
Facultad de Derecho y Ciencias Sociales. Maestría en Derecho
Keywords: info:eu-repo/classification/cti/5; FDCS-M-2021-1514; Amparo indirecto; Perspectiva práctica; Recursos; Incidentes; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/6378